Взаємодія з громадськими об’єднаннями як принцип діяльності Національної поліції - Комзюк, А. В.; Komziuk, A. V.; ORCID: http://orcid.org/0000-0002-2615-103X (Вісник Харківського національного університету внутрішніх справ. - 2016. - № 4 (75). - С. 147–155, 2016)
Проаналізовано взаємодію з громадськими об’єднаннями як принцип діяльності поліції. Визначено поняття, зміст, нормативні засади, форми зазначеної взаємодії, а також її значення для виконання Національною поліцією своїх завдань та функцій, зокрема щодо протидії правопорушенням.

This article is focused on the analysis of the interaction with public associations as a principle of the police activities in order to form and determine the content, forms of the stated interaction and its significance to perform the duties and functions by the National Police, in particular to combat offenses. The author has offered a definition of the term of “interaction”, which should be perceived according to the author as a process of the impact of various objects at each other, their mutual conditionality, change of the state, mutual transformation and the generation of one object by another one. Special attention is paid to the fact that such work should be based on the principles of the police activities. The main principles is the rule of law, keeping human rights and freedoms, justice, openness and transparency, political neutrality, interaction with the population based on the partnership principles, continuity. The significance of realizing the tasks and functions of the police activities finds its external identification in the relevant forms that are defined by the type of relationship in a particular area of human activity. Based on the conducted research the author has formed the classification of the forms that are the most common for the mutual activities of police officers and population in the sphere of keeping public order and combating crimes.

Проанализировано взаимодействие с общественными объединениями как принцип деятельности полиции. Определены понятие, содержание, нормативные основы, формы указанного взаимодействия, а также его значение для выполнения Национальной полицией своих задач и функций, в частности, по противодействию правонарушениям.
Взаимодействие с общественными объединениями как принцип деятельности Национальной полиции
Interaction with NGOs as the principle of the activities of the National police
Комзюк, А. В. Взаємодія з громадськими об’єднаннями як принцип діяльності Національної поліції / А. В. Комзюк // Вісник Харківського національного університету внутрішніх справ. - 2016. - № 4 (75). - С. 147–155.
Комзюк А. В. "Взаємодія з громадськими об’єднаннями як принцип діяльності Національної поліції." Вісник Харківського національного університету внутрішніх справ 4 (2016): 147-155.
Komziuk, A.V. (2016), “Interaction with NGOs as the principle of the activities of the National police” [Vzaiemodiia z hromadskymy obiednanniamy yak pryntsyp diialnosti Natsionalnoi politsii], Visnyk Kharkivskoho Natsionalnoho Universytetu Vnutrishnikh Sprav, No. 4, pp. 147–155.
Keywords: Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Національна поліція України. National police of Ukraine. Национальная полиция Украины; громадські об’єднання; взаємодія; правопорушення; протидія правопорушенням; public associations; National police of Ukraine; interaction; offenses; counteraction; поліція; полиция; police; Национальная полиция Украины; общественные объединения; взаимодействие; правонарушения; противодействие